Identification and Characterization of N6-Methyladenosine CircRNAs and Methyltransferases in the Lens Epithelium Cells From Age-Related Cataract - Li, Pengfei; Yu, Hualin; Zhang, Guowei; Kang, Lihua; Qin, Bai; Cao, Yu; Luo, Jiawei; Chen, Xiaojuan; Wang, Ying; Qin, Miaomiao; Wu, Jian; Huang, Yemeng; et al. (Investigative ophthalmology & visual science, 2020)
To explore the involvement of N6-methyladenosine (m6A) modification in circular RNAs (circRNAs) and relevant methyltransferases in the lesion of lens epithelium cells (LECs) under the circumstances of age-related cataract (ARC). LECs were collected from normal subjects and patients with cortical type of ARC (ARCC). M6A-tagged circRNAs and circRNAs expression were analyzed by m6A-modified RNA immunoprecipitation sequencing (m6A-RIP-seq) and RNA sequencing (RNA-seq). Gene Ontology (GO) annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were used to predict possible functions of the m6A-circRNAs. Expression of m6A-related methyltransferase and demethytransferase was measured by quantitative real-time polymerase chain reaction. Expression and location of AlkB homolog 5 RNA demethylase (ALKBH5), a key component of m6A demethytransferase, were determined by Western blot and immunostaining. All 4646 m6A peaks within circRNAs had different abundances, with 2472 enriched and 2174 subdued. The level of m6A abundance in total circRNAs was decreased in the LECs from ARCCs in comparison with the controls. We also found that the expression of highly m6A-tagged circRNAs was mostly decreased in comparison with non-m6A-tagged circRNAs. The bioinformatics analysis predicted the potential functions of m6A modified circRNAs and the relevant pathways that may be associated with m6A modified circRNAs. Among five major methyltransferases, ALKBH5 was significantly upregulated in LECs of ARCCs. Our data provided novel evidence regarding the involvement of circRNAs m6A modifications in ARC. The altered expression of methyltransferases in lens tissue might selectively change the epigenetic profile of lens genome through regulating genes that host the circRNAs, thus enhance the susceptibility to ARC. The results might provide a new insight in the molecular target of ARC pathogenesis.